Simultaneous determination of abiraterone and its five metabolites in human plasma by LC-MS/MS: Application to pharmacokinetic study in healthy Chinese subjects - Hu, Yixin; Wu, Jianyuan; Jiang, Xin; Chen, Guiying; Zhang, Yang; Si, Luqin; Jiang, Hongliang; Huang, Jiangeng; Huang, Jianying (Journal of pharmaceutical and biomedical analysis, 2022)
In this study, a rapid, simple and sensitive liquid chromatography–tandem mass spectrometry (LC-MS/MS) method was developed and validated to simultaneously quantify abiraterone (ABI), a widely used anti-metastatic castration-resistant prostate cancer drug, and its metabolites comprising Δ4-abiraterone (D4A), 3-keto-5α-abiraterone (5αA), abiraterone N-oxide (A-NO), abiraterone sulfate (A-Sul) and abiraterone N-oxide sulfate (A-NO-Sul) in human plasma. The analytes were extracted by protein precipitation with acetonitrile and ideal chromatographic separation was achieved on ACE-C18 column (2.1 × 50 mm, 5 µm) using a gradient elution. Triple Quad™ 6500+ mass spectrometer equipped with an electrospray ionization (ESI) source was used and the multiple reaction mode (MRM) was performed. In terms of method validation, good linearity was observed in preassigned validated concentration range for each analyte of interest. Both intra- and inter-batch accuracy was within the range of 87.6–113.8% for all analytes, while intra- and inter-batch precision was below 14.0%. Additionally, both low matrix effects and high recovery were obtained. All analytes remained stable in human plasma at room temperature for 4 h, on wet ice for 8 h, at − 80 °C for 42 d, over three freeze-thaw cycles and under auto-sampler temperature (4 °C) for 48 h post sample preparation. Subsequently, the validated LC-MS/MS method was applied for pharmacokinetic study in healthy Chinese volunteers following an oral dose of 250 mg abiraterone acetate tablet under fasted conditions. Our study for the first time reported the pharmacokinetic parameters of the ABI metabolites in Chinese subjects. •An LC-MS/MS method for quantifying abiraterone and its five metabolites in plasma.•Separate sets of calibrators were constructed to avoid interference among analytes.•Lowering temperature increased the stability of abiraterone and 3-keto-5α-abiraterone.•Abiraterone and its five metabolites manifest distinct pharmacokinetic profiles.